Inflatable Robotics Arm Capable of Deploying and Retracting by Rolling for High-Packaging Ratio - Kim, Changhwan; Shin, Dongwook; Back, Inryeol; Kim, Dongjin; Choi, Damin; Han, Seungyong; Kang, Daeshik; Koh, Je Sung (2024 IEEE 7th International Conference on Soft Robotics, RoboSoft 2024, 2024)
For robots to be useful for real-world applications, they should be safe around humans, deployable and passively compressible to a fraction of their size, and low-cost for practical use. A soft robotic arm potentially meets these requirements. The space efficiency of the soft robotic arm can be greatly enhanced by making it retractable. Here, we introduce an inflatable robotic arm capable of both deployment and retraction by rolling out from a small package and rolling in. We have conducted experiments characterizing the performance of the bellows actuator in torque, angle, and pressure. We also demonstrate that the rolling mechanism, based on the bilayer film, occupies minimal space when stowed, but can be deployed to access a large workspace. In addition, we demonstrate the feasibility of the inflatable robotic arm through the pick-and-place function to clear objects on the floor.
Keywords: Low-costs; Mechanism-based; Performance; Practical use; Real-world; Rolling mechanism; Small package; Soft robotics; Space efficiencies; Torque angle